Intraocular Pressure Measured by Rebound Tonometry in Seven Raptor Species - YÖNEZ, Muhammed Kaan; Erol, M; Erol, H; Atalan, G; Doğan, Z; Kibar, M (Journal of the Hellenic Veterinary Medical Society, 2022)
In the present study, intraocular pressures (IOP) of 66 Buzzards (132 eyes), 20 Hawks (40 eyes), 13 Owls (26 eyes), 6 Eagles (12 eyes), 6 Kestrels (12 eyes), 4 Falcons (8 eyes), 2 Vultures (4 eyes), which referred to Erciyes University, Faculty of Veterinary Medicine, Department of Surgery Clinic were evaluated. In the ophthalmologic examination there was no lesion detected related to eyes. The mean body weight raptors was 1.10±0.23 kg (Buzzards), 0.23±0.06 kg (Hawks), 0.27±0.10 (Owls), 3.30±0.80 kg (Eagles), 0,18±0.04 kg (Kestrels), 0,64±0,28 kg (Falcons) and 2.28±0.43 kg (Vultures). Rebound tonometer (Tonovet) was used for measurement of IOP. Mean intraocular pressures of right and left eyes were in Buzzards 25.87±0.62-26.61±0.71, Hawks 11.90±0.40-12.05±0.41, Owls 12.00±0.63-12.61±0.57, Eagles 29.00±2.89-30.33±2.87, Kestrels 11.75±0.17-10.83±0.47, Falcons 14.75±1.10-14.25±0.85 and Vultures 15.00±1.00-14.50±0.50. As a result of the study, repeated intraocular pressure measurements of raptors can be made by using rebound tonometer. In addition, the application of rebound tonometer is very easy to application do not require local anaesthetic. Therefore, raptors may be able to tolerate the application easily. The present data are considered to contribute to the literature.